Sarah Cottier Gallery Sydney 1997. (Sydney : Sarah Cottier Gallery, 1997)
Group Otto ; May, Anne-Marie ; Gerber, Matthys ; Nixon, John ; Poliness, Kerrie ; Georgetti, Diena ; Miller, Gerold ; Donaldson, A.D.S. ; Williams, Justene ; Cruz, Maria ; Armanious, Hany ; Armleder, John ; Dashper, Julian ; Donaldson, A.D.S. ; Dwyer, Mikala ; Fleury, Sylvie ; Mosset, Olivier ; Reiter Raabe, Andreas ; Williams, Justene
Engels
boek